2018
DOI: 10.5194/gmd-2018-279
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Improvements to stratospheric chemistry scheme in the UM-UKCA (v10.7) model: solar cycle and heterogeneous reactions

Abstract: Abstract. Improvements are made to two areas of the United Kingdom Chemistry and Aerosol (UKCA) module, which forms part of the Met Office Unified Model (UM) used for weather and climate applications. Firstly, a solar cycle is added to the photolysis scheme. The effect on total column ozone of this addition was found to be around 1–2 % in mid-latitude and equatorial regions in phase with the solar cycle. Secondly, reactions occurring on the surfaces of polar stratospheric clouds and sulfate aerosol are updated… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 38 publications
2
5
0
Order By: Relevance
“…The changes to the stratospheric chemistry are tested by running the model for 30 years in a year 2000 time slice experiment using CMIP6‐prescribed trace gases and sea surface temperature forcings. The model is mostly able to reproduce the observed total column ozone and the results are similar to those found by Dennison et al (2019) in which a more thorough discussion of the changes can be found. The improved match with observed TCO resulting from our model updates is shown in Figure 1a.…”
Section: Methodssupporting
confidence: 83%
See 3 more Smart Citations
“…The changes to the stratospheric chemistry are tested by running the model for 30 years in a year 2000 time slice experiment using CMIP6‐prescribed trace gases and sea surface temperature forcings. The model is mostly able to reproduce the observed total column ozone and the results are similar to those found by Dennison et al (2019) in which a more thorough discussion of the changes can be found. The improved match with observed TCO resulting from our model updates is shown in Figure 1a.…”
Section: Methodssupporting
confidence: 83%
“…This could be due to the vortex breakup being delayed and is a known issue in a number of comprehensive chemistry‐ climate model (Butchart et al, 2011; Eyring et al, 2010; McLandress et al, 2012). Overall, our changes to the chemistry scheme lead to an ozone distribution that is very similar to Dennison et al (2019).…”
Section: Methodssupporting
confidence: 80%
See 2 more Smart Citations
“…As noted in section , UKESM1 includes photolytic reactions in its interactive simulation of ozone, but the photolysis rates use fixed solar inputs and therefore have no dependence on the solar variability. Dennison et al () show that including solar variability in photolysis calculations can have a noticeable effect on ozone production, resulting in variations of order 1% in extratropical total column ozone. This mode of ozone variability will therefore be absent from the UKESM1 CMIP6 simulations but will be a priority for inclusion in future versions of UKESM.…”
Section: Summary and Discussionmentioning
confidence: 99%